2020
DOI: 10.4103/jrpp.jrpp_20_98
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline in prevention of amphotericin B-induced nephrotoxicity and electrolyte abnormalities

Abstract: Objective: Amphotericin B is an antifungal agent used to treat serious fungal infections mainly in critically ill patients. Despite its adverse effects including renal toxicity and electrolyte imbalances, amphotericin B remains one of the best choices for antifungal treatment. Information from animal studies has provided a strong scientific basis for the use of pentoxifylline as lowering nephroprotective agent. The present study was designed to evaluate the efficacy of pentoxifylline in preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Among many studies, only saline loading and liposomal AmB have been shown to prevent or decrease AmB nephrotoxicity. However, both modalities have adverse effects like worsening of congestive heart failure and cirrhosis by saline intake and the high cost of lipid formulations associated also with some nephrotoxic effects and imbalance of electrolytes (Karimzadeh et al, 2020 , Panahi-Shokouh et al, 2020 ). That necessitates the search for novel modalities having pronounced efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Among many studies, only saline loading and liposomal AmB have been shown to prevent or decrease AmB nephrotoxicity. However, both modalities have adverse effects like worsening of congestive heart failure and cirrhosis by saline intake and the high cost of lipid formulations associated also with some nephrotoxic effects and imbalance of electrolytes (Karimzadeh et al, 2020 , Panahi-Shokouh et al, 2020 ). That necessitates the search for novel modalities having pronounced efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%